Variables influential on the return of cellular devices through reverse logistics - Pokriwieski, Lucas; Fagundes, Alexandre Borges; Beuren, Fernanda Hänsch; Vieira, Cleide; Kobs, Fábio Fernando; Vaz, Caroline Rodrigues (International Journal of Professional Business Review, 2025)
THIS IS AN ARTICLE PUBLISHED BY International Journal of Professional Business Review (e-ISSN: 2525-3654) ON 2025-02-20, AVAILABLE ONLINE: https://doi.org/10.26668/businessreview/2025.v10i2.5317 Abstract Objective: This study aimed to identify variables that affect the return of cell phones through reverse logistics, highlighting key factors in four research areas: compliance with standards, product useful life, consumer behavior issues, and the management of the reverse logistics system itself. Theoretical Framework: This section covers the definitions of electronic devices, material compositions, potential health risks, and factors affecting the return of these products to their origin through reverse logistics. Method: The approach used combines both qualitative and quantitative methods. Primary data collection was conducted through a structured survey, utilizing a five-point semantic scale. The data were analyzed in a quantitative, descriptive, and inferential manner. Results and Discussion: The results showed that Environmental Awareness, Access to Information, and Cost-Benefit of Maintenance— all factors directly related to Consumer Behavioral Issues—are the most critical points according to the majority of interviewees. Research Implications: The practical and theoretical implications of this research include a more comprehensive understanding of the factors that can influence the return of post-consumer products through reverse logistics. Originality/Value: This study adds to the literature by broadening the understanding of variables involved in the reverse logistics of cell phones. The relevance and value of this research are demonstrated by listing factors that influence the performance of reverse logistics systems, thereby providing insights for developing improvement strategies.
Keywords: Influencing Variables; Electronic Waste; Shelf Life; Environmental Responsibility; Reverse Logistics